The Role of Community Engagement in Balancing Tourism Growth and Environmental Sustainability: Evidence from Community-Based Tourism Destinations - Bayu Erwinadi; Irwan W (Jurnal Manajemen dan Inovasi Pariwisata, 2026)
Community engagement plays a crucial role in achieving sustainable tourism by balancing tourism growth with environmental sustainability. However, limited research has explored how community participation simultaneously supports economic development and environmental conservation within community-based tourism destinations. This study aims to examine the role of community engagement in fostering sustainable tourism development. A qualitative multiple case study approach was employed involving 25 participants, including local community leaders, tourism entrepreneurs, government officials, destination managers, and environmental organizations. Data were collected through semi-structured interviews, participant observation, focus group discussions, and document analysis, and analyzed using thematic analysis. The findings reveal four major themes: community participation strengthens tourism governance through inclusive decision-making; community-led initiatives enhance environmental stewardship; active engagement promotes inclusive tourism growth by creating local economic opportunities; and balancing tourism growth with environmental sustainability remains challenged by increasing tourism pressure, unequal participation, and institutional coordination. The study concludes that meaningful community engagement serves as a strategic governance mechanism linking tourism development with environmental conservation. The findings contribute to sustainable tourism literature by emphasizing collaborative governance and provide practical recommendations for policymakers and destination managers to strengthen community empowerment and participatory tourism planning.